Biomass-derived nanostructured carbons and their composites as anode materials for lithium ion batteries - Long, Wenyu; Fang, Baizeng; Ignaszak, Anna; Wu, Zhuangzhi; Wang, Yan-Jie; Wilkinson, David (Chemical Society reviews, 2017)
Since ever-increasing energy demands stimulated intensive research activities on lithium-ion batteries (LIBs), biomass as an earth-abundant renewable energy source has played an intriguing and promising role in developing sustainable biomass-derived carbons and their composite materials for high-performance LIB anodes. Different from other materials ( e.g. , silicon, tin, metal oxides, etc. ), biomass-derived carbons and their composite materials have been applied more and more to LIBs due to their advantages such as low cost, green and eco-friendly synthesis, easy accessibility, sustainable strategy, and improved battery performance, including capacity, cycling property, and stability/durability. This tutorial review focusing on biomass-derived carbons and their composites in the application of LIB anodes will act as a strategic guide to build a close connection between renewable materials and electrochemical energy storage devices. Also, this review provides a critical analysis and comparison of biomass-derived carbons and their composites for LIB anodes, coupled with an important insight into the remaining challenges and future directions in the field. This review focuses on the derivation of nanostructured carbons and their composite materials from biomass materials for lithium ion battery anodes.